THE INFLUENCE OF THE USE OF LEARNING MODEL MAKE A MATCH ON PROBLEM SOLVING ABILITY OF SPLDV SUBSTITUTE MATHEMATICS IN CLASS VIII OF SMP STATE 1 BATANG ANGKOLA - Saleh, Agus (Institut Pendidikan Tapanuli Selatan, 2018)
This study aims at finding out whether there is a significant influence of using make a match learning modelto mathematical problem solvingability on the topic of linear equation system of two variables at the eighth grade students of SMP Negeri 1 Batang Angkola. The research method in this study is experimental with 66 students as the sample. Descriptive and inferential analyzes were used to analyzed the data. Based on the data analysis, it was found that: (1)The average of mathematical problem solving ability on the topic of linear equation system of two variables using conventional learning is 69,95(enough category); (2) The average of mathematical problem solving ability on the topic of linear equation system of two variables using make a match learning modelis 82,59 (very good category), and (3) tcount is greater than ttable (5.91 >1699). It can be concluded that mathematical problem solving ability on the topic of linear equation system of two variables using make a match learning model is better than mathematical problem solving ability on the topic of linear equation system of two variables using conventional learning model at the eighth grade students of SMP Negeri 1 Batang Angkola